Patterns of rare earth and other trace elements in Paleogene and Miocene clayey sediments from the Mondego platform (Central Portugal) - Lisboa, J. Vítor (2016)
In the present study the origin of clay deposits occurring in an inland platform, in central Portugal, was investigated by their mineralogical and chemical composition. The clay deposits, exploited for ceramic industry are composed of silt-clay facies, the Monteira Member and the Arroça Member, which are assigned to the Coja Formation (Paleogene) and the Campelo Formation (Miocene), respectively. These clayey facies show almost compositional homogeneity, especially concerning texture. The mineralogical composition of the Monteira Member displays slightly higher content in smectite and interstratified clay minerals, which is supported by the chemical composition of samples analyzed. Both members present similar REE patterns, displaying an intense weathering record and little variation in the source area composition. Minor element geochemistry suggests low content in heavy minerals and transition metals. REE patterns and ratios of geochemical parameters support the dominant metasedimentary provenance, with a granite source contribution and also mature recycled sediments of continental origin. The study results’ suggest that the clays of these two members have the same source in terms of lithology and recycled sediments from the Hesperian massif. During the deposition of the Arroça Member, a major remobilization of the Monteira Member is suggested, explaining the geochemical similarity of both facies.